1979
DOI: 10.2307/1128928
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Sex Hormones in Umbilical-Cord Blood: Their Relation to Sex and Birth Order of Infants

Abstract: In 3 groups of human newborns, 5 sex hormones were assayed from samples of umbilical-cord blood, and concentrations were analyzed by the sex and birth order of the infants. The 5 hormones assayed were testosterone, androstenedione, estrone, estradiol, and progesterone. Concentrations of testosterone were significantly greater in males than females. The other 4 hormones did not differ significantly by sex. In both sexes, firstborns had significantly more progesterone and estrogens, with progesterone showing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(49 citation statements)
references
References 0 publications
3
46
0
Order By: Relevance
“…Findings on testosterone have been less consistent: levels in maternal and cord serum at term were not shown to be significantly different by offspring gender in some studies (43,47), whereas higher maternal and amniotic fluid levels in male bearers were found in others (48,49). Progesterone levels in maternal and fetal blood tend to be higher in male bearers than female bearers, although the difference was not significant (43,50). Studies that measured 17-hydroxyprogesterone, a metabolite of progesterone, have found significantly higher blood levels in males than in female newborns (51), particularly among the full-term deliveries (52).…”
Section: Offspring Gender and Maternal Risk Of Ovarian Cancer Cancer mentioning
confidence: 99%
“…Findings on testosterone have been less consistent: levels in maternal and cord serum at term were not shown to be significantly different by offspring gender in some studies (43,47), whereas higher maternal and amniotic fluid levels in male bearers were found in others (48,49). Progesterone levels in maternal and fetal blood tend to be higher in male bearers than female bearers, although the difference was not significant (43,50). Studies that measured 17-hydroxyprogesterone, a metabolite of progesterone, have found significantly higher blood levels in males than in female newborns (51), particularly among the full-term deliveries (52).…”
Section: Offspring Gender and Maternal Risk Of Ovarian Cancer Cancer mentioning
confidence: 99%
“…A possible reason for this negative effect of birth order on the birth weight is that the mother's health may have been weakened as a result of many pregnancies and years of caring for children. This idea is somewhat medically supported in that it is believed that the growth of the baby during pregnancy is affected by the mother's levels of hormones and insulin-like growth factors; which tend to reduce at very high parities (D'Ercole and Ye 2008; Skalkidou et al 2003;Beyer 1999;Reece et al 1994;Panagiotopoulou et al 1990;Maccoby et al 1979).…”
Section: Determinants Of Birth Weight and Estimation Strategymentioning
confidence: 99%
“…Based on findings indicating that levels of circulating progesterone increase with longer time between births, the present study tested whether the wider birth spacing for a given parity reduces the risk of ovarian cancer. With repeated pregnancies and close spacing between births, time may be too short for the recovery of certain maternal physiological processes involved in gestation and, as a result, the placenta may not be as active in producing progesterone [17].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the association with certain reproductive factors that reflect circulating levels of progesterone during pregnancy has been examined to lend indirect support and several epidemiologic studies have shown a greater risk reduction of epithelial ovarian cancer for the first birth than for subsequent births [2][3][4][5][7][8][9][10]. These findings are compatible with the physiological observation that first-born infants have higher progesterone levels in umbilical cord blood than later-borns [17].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation